A cylindrical Barium Strontium Titanate (BST) dielectric resonator antenna for 5.0 GHz wireless LAN application - Azremi, Abdullah Al Hadi (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org